2016
DOI: 10.11130/jei.2016.31.4.817
|View full text |Cite
|
Sign up to set email alerts
|

Causal Nexus between Financial Integration and Economic Growth : Does Nonlinearity Matter?

Abstract: Empirical studies that rely on a linear framework typically fail to find evidence of a causal link between financial integration and economic growth. In this study, we extend the analysis by applying both linear and nonlinear Granger-causality tests to data for 19 emerging and developing countries. Consistent with previous research, the linear causality analysis reveals only weak causal linkages between financial integration and economic growth. In contrast, the nonlinear causality analysis provides evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…And finally, we analyze the Toda-Yamamoto approach (Toda and Yamamoto, 1995). These authors step forward with the Granger causality approach and use the modified Wald test (MWALD), based on a VAR(k + d max ) model where k is the optimal order of system lags, and d max is the maximum order of model integration (Saafi et al, 2016). This approach includes additional lags to consider the non-stationarity of the series, and the number of additional lags is based on the order of integration of the series.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And finally, we analyze the Toda-Yamamoto approach (Toda and Yamamoto, 1995). These authors step forward with the Granger causality approach and use the modified Wald test (MWALD), based on a VAR(k + d max ) model where k is the optimal order of system lags, and d max is the maximum order of model integration (Saafi et al, 2016). This approach includes additional lags to consider the non-stationarity of the series, and the number of additional lags is based on the order of integration of the series.…”
Section: Methodsmentioning
confidence: 99%
“…The VAR can be used in non-stationary series (Andersson et al, 2016). Saafi et al (2016) used this approach to analyze causality between financial integration and economic growth for a group of 19 developing and developed countries. Andersson et al (2016) analyzed causality between the banking sector and Chinese economic growth with the Toda-Yamamoto approach.…”
Section: Methodsmentioning
confidence: 99%
“…Methodologically, the impact of financial integration on economic growth could differ between linear or non-linear frameworks. Saafi et al (2016) investigated the causal relationship between financial integration and economic growth within linear and non-linear frameworks in 19 developing and emerging economies. In the linear causality analysis, the study found a weak causal relationship between integration and growth.…”
Section: Studies On Significant Positive Effects Of Financial Integration On Economic Growthmentioning
confidence: 99%
“…Hence, several developing and emerging economies have embarked on a rapid process of financial integration in the past few decades. This is because financial integration has the capacity to promote capital allocation, production specialization, international consumption risk-sharing, and economic growth (Acemoglu & Zilibotti, 1997;Gehringer, 2015;Obstfeld, 1994;Saafi et al, 2016). Besides, financial integration improves factor productivity via greater efficiency in resources allocation and easy access to investment opportunities thereby stimulating economic growth (Edison et al, 2002;Gehringer, 2013;Giannetti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Prasad et al (2007) In the case of developing countries, the integration-growth nexus is found to be unclear (Eichengreen 2002, Saafi et al 2016. Despite the limited work on the region, the financial integration process has been widely debated across Asia, Middle East, and Latin America.…”
Section: Literature Reviewmentioning
confidence: 99%